2014
DOI: 10.1073/pnas.1412081111
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor binding predicts histone modifications in human cell lines

Abstract: Gene expression in higher organisms is thought to be regulated by a complex network of transcription factor binding and chromatin modifications, yet the relative importance of these two factors remains a matter of debate. Here, we show that a computational approach allows surprisingly accurate prediction of histone modifications solely from knowledge of transcription factor binding both at promoters and at potential distal regulatory elements. This accuracy significantly and substantially exceeds what could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 42 publications
(46 reference statements)
9
86
0
Order By: Relevance
“…These studies reported increased performances in the sequence-based Cold Spring Harbor Laboratory Press on May 12, 2018 -Published by genome.cshlp.org Downloaded from modeling of in vivo TF binding events when such models incorporated HMs (Benveniste et al 2014;Liu et al 2015a). In this study, we described qualitatively and quantitatively the relationship between TF binding and HM patterns in a protein family-specific manner across different cell lines.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These studies reported increased performances in the sequence-based Cold Spring Harbor Laboratory Press on May 12, 2018 -Published by genome.cshlp.org Downloaded from modeling of in vivo TF binding events when such models incorporated HMs (Benveniste et al 2014;Liu et al 2015a). In this study, we described qualitatively and quantitatively the relationship between TF binding and HM patterns in a protein family-specific manner across different cell lines.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies reported a quantitative relationship between in vivo TF binding specificities and HM patterns surrounding BSs near DNA regulatory elements (Benveniste et al 2014;Liu et al 2015a). Given our qualitative observation that HM pattern preferences surrounding BSs are protein family-specific, an obvious question is whether HM patterns at TF BSs can add another layer to modeling genome-wide in vivo TF binding quantitatively in a protein family-specific manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, computational analysis combined with chromatin immunoprecipitation followed by sequencing (ChIP-Seq) revealed that transcription factor binding predicts histone modifications in human cell lines (43), but the role of transcription factor in histone modifications over specific gene promoters has not been experimentally demonstrated. Our data showed that sequencespecific transcription factor regulates gene expression not only by recognizing specific DNA sequences, but also by facilitating histone modifications such as H3K4me3 at specific DNA sites through interaction with the COMPASS-like components Ash2 and WDR5a (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bieberstein and colleagues showed intriguing patterns of accumulation of the histone marks H3K4me3 and H3K9ac at splice sites [5], hinting at an architectural origin of the shape of the marks. More recently, Benveniste et al showed that histone marks can be very well predicted genome-wide by the binding patterns of transcription factors (TFs) [6]. The shape of the peak may therefore be a readout of additional chromatin-related events and genomic regions which are similarly marked may therefore hint at common regulatory or architectural features.…”
Section: Introductionmentioning
confidence: 99%